Survei Kepadatan dan Identifikasi Jentik Nyamuk Aedes Aegypti Sebagai Vektor RT 005 Pesisir Pantai Wailela Desa Rumah Tiga Kecamatan Teluk Ambon - Arfan Ohorella; Kasman Lestaluhu; Amry Jusuf (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Aedes aegypti mosquito is the cause of Dengue Hemorrhagic Fever (DHF) which can cause outbreaks and result in high vector development due to uncontrolled vector development. To determine the density and identification of Aedes aeygpti mosquito larvae as vectors RT 005 RW 014 Wailela coastal environment, Rumah Tiga Village, Teluk Ambon District, Descriptive survey research using the cross sectonal method. This research was carried out in the coastal area of RT 005 RW 014 Rumah Tiga Village, Teluk District. In this study, the population taken was 48 houses located in the coastal area of RT 005 RW 014 Rumah Tiga Village, Teluk Ambon District. The variables of this study used larval indices (house index, container index, breteauIndex). The results of the study showed that the assessment of House Index (HI) = 97% Container Index (CI) = 46% and Breteu Index (BI) = 308% with DF= which showed that the density of larvae in the coastal area of RT 005 RW 014 Rumah Tiga Village was quite high and the risk of transmission was also high. Based on the results of the survey, Aedes aegypti mosquito larvae are more commonly found in dispensers and flower pots compared to other types of containers. According to the results of a research survey conducted on the Aedes aegypti mosquito larvae survey in the coastal area of RT 005 RW 014 Rumah Tiga Village, Teluk Ambon District in 2024, the following conclusions were obtained: From the House Index (HI) inspection, 97% of the 46 houses inspected, from the Co M. Interner Index (CI) inspection, 46% positive of the 46 houses inspected, From the Breteu Index (BI) inspection, 308% of the 47 houses inspected.